Pengaruh perbedaan bentuk tempat pakan terhadap performa puyuh padjadjaran petelur fase brooding - Fanya Nur Haryani; Endang Sujana; Iwan Setiawan (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This research purpose was to determine the effect of different feeder shape on performance of Padjadjaran Layer Quails in the brooding phase. This research was held in the Quail Breeding Center, Faculty of Animal Husbandry, Padjadjaran University used 360 male and female black line of Padjadjaran Layers Quail. There were 18 treatment cages, each cage unit containing 20 quails. This research used Completely Randomized Design (CRD) there were 3 treatments and repeated 6 times. The treatment given to quail from 1 until 3 weeks of age consisted of trough feeder (P1), baby chick feeder (P2) and feeder tray (P3).  Data of feed consumption, body weight gain, and feed convertion ratio were analyzed using variance and Duncan’s Multiple Range Test. Total feed consumption is as follow 240,59 gram, 257,38 gram, and 247,55 gram. Each successive body weight gais is as follow 84,20 gram, 109,57 gram, and 98,47 gram. Average of feed convertion ratio is as follow 2,87; 2,39; and 2,52. The conclusion from result showed that the different feeder shape affected on performance of Padjadjaran Layer Quails in the brooding phase. Baby chick feeder provides good performance for laying Padjadjaran quail in the brooding phase.